Reasons behind discontinuation of BRAC teachers in Non-Formal Primary Education programme - Khan, Kaisar A (BRAC Research and Evaluation Division (RED), 2020)
This study aimed at examining the reasons of discontinuation of NFPE teachers. To achieve the objective, 259 dropped out and 252 in-service teachers were interviewed from two former NFPE regions through a semi-structured questionnaire. Beside this, to collect qualitative information, 16 focus group discussions with the NFPE staff and the in-service: teachers were conducted. The findings show that teacher's discontinuation was frequently not related to a single factor, but rather a contribution of several socio-cultural, personal and organisational factors was responsible. These factors included: physical illness, poor remuneration, extensive household chores, workload with the school-related activities and pedagogical weakness of the teachers. It was realized that the stated factors were not directly associated with the discontinuation. These factors reduced the motivational level of the teachers as well as their attachment towards the job. As the job was insecure and had no future prospect the teachers gave lesser priority to the continuation of their service.